Endothelial Cell Regulation of Pulmonary Vascular Tone, Inflammation, and Coagulation. Issue 2 (16th March 2015) - Goldenberg, Neil M.; Kuebler, Wolfgang M.
ABSTRACT: The pulmonary endothelium represents a heterogeneous cell monolayer covering the luminal surface of the entire lung vasculature. As such, this cell layer lies at a critical interface between the blood, airways, and lung parenchyma, and must act as a selective barrier between these diverse compartments. Lung endothelial cells are able to produce and secrete mediators, display surface receptor, and cellular adhesion molecules, and metabolize circulating hormones to influence vasomotor tone, both local and systemic inflammation, and coagulation functions. In this review, we will explore the role of the pulmonary endothelium in each of these systems, highlighting key regulatory functions of the pulmonary endothelial cell, as well as novel aspects of the pulmonary endothelium in contrast to the systemic cell type. The interactions between pulmonary endothelial cells and both leukocytes and platelets will be discussed in detail, and wherever possible, elements of endothelial control over physiological and pathophysiological processes will be examined. © 2015 American Physiological Society. Compr Physiol 5:531‐559, 2015.